The Legitimacy of Presidential Threshold Towards Indonesian Citizens’ Democracy and Constitutional Rights - Imam Pratama Rifky (Fakultas Hukum Universitas Lampung, 2021)
A presidential threshold or a threshold for presidential candidacy dramatically hinders a person's democratic rights. This is because a person can rightfully nominate and elect themselves through a political party, which must be limited due to this system. The Presidential Threshold could eliminate the fundamental rights of the people in the constitution, where every citizen has the right to be elected and to vote. This statement is stated in Article 28(D) paragraph 3 of the 1945 Constitution, later revealed to be Law No.39 of 1999. With the existence of this presidential threshold, it is feared that it could injure the law's mandate. The research aims to determine whether the presidential threshold injured democracy and the mandate of the 1945 constitution. This research uses a normative approach. The research will focus on the principles, comparisons and history of law. The presidential threshold will close the space for political parties to carry the best presidential and vice-presidential candidates for the community. This automatically kills democracy, political parties' constitutional rights, and the people's right to choose the best and quality, leaders.